A settlement pattern study in northeast China : results and potential contributions of western theory and methods to Chinese archaeology - Shelach, Gideon
Chinese scholarship well illustrates how research attitudes direct the spirit of research, and the tenor of the archaeological story which results. What happens when non-Chinese theory, approaches and field methods are brought to bear in a Chinese regional study?